Chemically Activated SS Metathesis for Adhesive‐Free Bonding of Polysulfide Surfaces. Issue 13 (23rd November 2021) - Mann, Maximilian; Pauling, Paris J.; Tonkin, Samuel J.; Campbell, Jonathan A.; Chalker, Justin M.
Abstract: A polysulfide terpolymer made from canola oil, dicyclopentadiene, and elemental sulfur is synthesized and evaluated as bulk structural material. The unique polysulfide structure in this material allows the two polymer blocks to be bonded together through amine‐catalyzed SS metathesis. No exogenous adhesive is required: the polysulfide is both the bulk material and the mortar. The strength of the joined polymers is evaluated by a series of shear tests and compared to the bond strength obtained with commercially available superglue. The adhesion obtained via the SS metathesis is stronger in all tests. To improve the mechanical properties of the terpolymer, carbon nanorods and carbon fibers are embedded in the polymer, with the latter leading to nearly a 16‐fold increase in flexural strength. Prospects in sustainable construction are discussed. Abstract : A terpolymer is made from renewable or low‐cost materials canola oil, dicyclopentadiene, and sulfur. Using a triethylamine catalyst, the polymers can be bonded together by SS metathesis, without the use of any exogenous adhesive. By using carbon fiber additives, the flexural strength of the material is greatly increased. Prospects in sustainable construction are examined.